(untitled) (The Himalayan Geographers, 2023)
The terms "land use" and "land cover" pertain to two related ideas about how the earth’s surface is covered. While land use refers to the socioeconomic framework and purpose that enable human activity on the land. Land cover refers to the natural or ecological state of the land. Since land is a valuable and limited resource, knowledge of changes in land cover and use is crucial for determining how human activity affects the ecosystem. This study examined the state of land cover change and land use at Hemja, a location within the Pokhara Metropolitan City, over a 20-year period. Direct observation, topographic map verification, surveys, focus group discussions, and interviews were the methods used to gather primary data. Through a variety of governmental and non-governmental sources, secondary data were gathered. The results of the study were obtained by statistical and geographical analysis of this data. The conversion of agricultural, woodland, bush, and sandy areas into built-up areas was one of the study area’s most noticeable changes. Various issues related to infrastructure, economy, and demography have been proposed as the reasons behind this shift in the study area across the historical period. Additional research micro level could be useful in examining the specific effects of the causes and estimating the potential effects of such changes in land use and land cover.